Effect of Heat Treatment on Physical and Mechanical Properties of Cemented Carbide and Carbon Steel Brazed Joints - Yoyok Winardi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
Cemented carbides are joined with steel to be used as a cutting tool. Brazing is one of a method joinning metals that has the potential to combine different types of materials such as cemented carbide and steel. This study aimed to investigate the effect of heat treatment on the microstructure and the distribution of the hardness value brazed joint between cemented carbide and carbon steel. The heat treatment was carried out at a temperature of 700oC, 725oC, and 750oC for 30 minutes. The joint area is observed using SEM equipped with EDS. The distribution of hardness value ​​was tested using a micro vickers testing machine. Microstructure observations and SEM-EDS analysis show that the junction region consists of 3 parts, part I is the phase of Cu solution enriched solid, part II phase of the solid solution with the highest percentage of Ag, and part III is the eutectic phase of Ag-Cu-Zn . EDS test results in each section show that the value of element C increases when the treatment temperature is increased. The hardness test results show that the distribution of the hardness value increases when the treatment temperature is added. The hardness of the test specimen without treatment reached 112.73 VHN. The highest hardness value is 131.88 VHN at 750oC. Thus the heat treatment affects the microstructure and the rate of diffusion of metal elements. The higher the temperature, the diffusion rate of the metal element increases, so that it affects mechanical.